2019
DOI: 10.3390/ijms20061286
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Induces EBV Lytic Reactivation through ADORA1 in EBV-Associated Gastric Carcinoma

Abstract: Cordyceps species are known to contain numerous bioactive compounds, including cordycepin. Extracts of Cordyceps militaris (CME) are used in diverse medicinal purposes because of their bioactive components. Cordycepin, one of the active components of CME, exhibits anti-proliferative, pro-apoptotic, and anti-inflammatory effects. Cordycepin structurally differs from adenosine in that its ribose lacks an oxygen atom at the 3′ position. We previously reported that cordycepin suppresses Epstein–Barr virus (EBV) ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Moreover, the canonical NF-κB signalling pathway is constitutively activated, and this plays an essential role in EBVaGC tumorigenesis 16 . ADORA1 has been reported to suppress BZLF1 induction, increase tumour cell growth with EBV infection and inhibit sensitivity to the cytotoxic effects of antiviral and anticancer agents 17 . Thus, therapy selection based on the mechanism of tumour development is required, and it is important to diagnose EBVaGC prior to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the canonical NF-κB signalling pathway is constitutively activated, and this plays an essential role in EBVaGC tumorigenesis 16 . ADORA1 has been reported to suppress BZLF1 induction, increase tumour cell growth with EBV infection and inhibit sensitivity to the cytotoxic effects of antiviral and anticancer agents 17 . Thus, therapy selection based on the mechanism of tumour development is required, and it is important to diagnose EBVaGC prior to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[43][44][45][46] Recent reports on cancers of epithelial origin indicate that, in addition to nasopharyngeal cancer, EBV infection is also closely associated with approximately 10% of gastric cancers, which are known as EBV-associated gastric carcinomas (EBVaGC). 47,48 In addition, recent studies have revealed an association between EBV infection and certain breast cancers. 49 EBV was the first virus to be identified as an oncogenic virus, and as the spectrum of cancers caused by this virus widened, mechanisms underlying its pathogenicity came under increasing scrutiny.…”
Section: Discussionmentioning
confidence: 99%
“…EBV infection is a direct cause of NPC, which is invasive and metastatic, often resulting in death 43‐46 . Recent reports on cancers of epithelial origin indicate that, in addition to nasopharyngeal cancer, EBV infection is also closely associated with approximately 10% of gastric cancers, which are known as EBV‐associated gastric carcinomas (EBVaGC) 47,48 . In addition, recent studies have revealed an association between EBV infection and certain breast cancers 49 .…”
Section: Discussionmentioning
confidence: 99%
“…The following cycles thermal conditions were used: 95°C for 10 min; cycles of 95°C for sec, 55°C for 10 sec, and 72°C for 10 sec; 95°C for 5 sec; followed by 65°C for 1 min. In case of necessity, semi-quantitative PCR (sqPCR) was also conducted as previously described [37]. PCR products were amplified in a 25 µL reaction solution containing 5 µL of 5× reaction mix, 5 µL of 5× TuneUp solution, 1 µL of Taq-plus polymerase, and 2.5 µL of 10 pmol forward/reverse primer.…”
Section: Real-time Quantitative Pcr (Qpcr)mentioning
confidence: 99%